STRATEGI RELAKSASI UNTUK MEMBANTU SISWA YANG MENGALAMI STRES BELAJAR DI KELAS 9D SMP NEGERI 1 MEJAYAN KABUPATEN MADIUN - Pramunto, Bambang Agus (Jurnal Counsellia, 2015)
Along with the advancement of science and technology, the problems faced by individuals increasingly complex. A problem that can not be avoided by students in general and students in grade 9 in particular is a matter of learning. Slowly but surely grade 9 students have to face the "Monster" in completing his education at the junior high school is very popular so-called UN. Phenomena in the field seen many students are scrambling to prepare. They forge themselves participate tutoring outside of school and at school, and a number are still calling a tutor Even more ironic ladies and teachers provide enormous task. Classroom Action Research (CAR) is implemented in order to help students overcome problems related to distress (stress) on the learner as tired of learning. Help is alleviation, with the expectation that students face problems (stress learning) can understand yourself, set yourself and can eventually adapt to the problems that it faces.Relaxation strategy is one of the techniques in guidance and counseling services aimed at helping students to release tension and fatigue in this case is the state of stress related to learning activities.Research methods by using several instruments including a questionnaire (stress questionnaire study), namely Stress Questionnaire Learning is used to determine and measure the students who have studied the stress levels encountered during the pre-test and post-test, manual observation and interview guidelines.Technical analysis of the data, using qualitative analysis, but also supported by quantitative analysis. Quantitative analysis is used when processing data Stress Study questionnaire in order to determine the level of stress category learning experienced by learners.In this study there are two cycles. Conclusions on pre-research activities outlined in the initial reflection. Keywords: Learning Stress, Relaxation